Intracranial non-germinomatous germ cell tumors in children and adolescents: how can the experience from an uppermiddle-income country contribute to the worldwide effort to improve outcomes? - Cappellano, Andrea M.; Dassi, Natalia; Mançano, Bruna M.; Epelman, Sidnei; Almeida, Daniela B.; Cavalheiro, Sergio; Dastoli, Patricia A.; Alves, Maria T. S.; Nicacio, Jardel M.; Costa, Marcos D. S.; Silva, Frederico A.; Aguiar, Simone S.; et al. (Frontiers in Oncology, 2024)
Background: Non-germinomatous germ cell tumors (NGGCT) accounts for one third of intracranial GCT. While the germinoma group have an excellent overall survival, the standard of practice for children with NGGCT is still under evaluation. Aims: Describe the results of the of the Brazilian consortium protocol. Methods: Since 2013, 15 patients with a diagnosis of NGGCT by histopathology and/or serum/cerebrospinal fluid (CSF) tumor markers, βHCG >200mlU/ml and/or positive alpha-fetoprotein were treated with neoadjuvant chemotherapy with carboplatin, cyclophosphamide and etoposide followed by ventricular radiotherapy (RTV) of 18Gy with boost (32Gy) to the primary site. Metastatic patients underwent craniospinal irradiation (CSI) and “slow responders” to the four initial cycles of CT, to autologous stem cell transplantation (ASCT) followed by CSI. Results: Mean age, 13.1 years. Thirteen males. Primary sites: pineal (n=12), suprasellar (n=2) and bifocal (n=1). Four patients were metastatic at diagnosis. Eight patients had CSF and/or serum alpha-fetoprotein levels > 1,000ng/ml. Tumor responses after chemotherapy demonstrated complete in six cases and partial in seven, with "second-look" surgery being performed in five cases, and two patients presenting viable lesions being referred to ASCT. The main toxicity observed was hematological grades 3/4. Two patients with metastatic disease, one with Down Syndrome and AFP > 1,000ng/ml and the other with choriocarcinoma and pulmonary metastases, developed progressive disease resulting in death, as well as two other patients without evidence of disease, due to endocrinological disorders. Event-free and overall survival at 2 and 5 years were 80% and 72.7%, respectively, with a mean follow-up of 48 months (range, 7-107). Conclusions: Despite the small number of patients, in our series, treatment with six cycles of chemotherapy and RTV with focal boost for localized disease (n=11) and ACST for identified slow responders (n=2) seem to be effective strategies contributing to the overall effort to improve outcomes of this group of patients.